An overview of knee osteoarthritis severity in Pandanwangi, Malang - Prastowo, Bayu; Bai, Matilda Novian; Prameswari, Ni Nyoman Diah; Wiraningtyas, Tria Hesti; Rassamee, Nichapat; Chieochansin, Kanyamon; Ertitri, Fika (Journal of Community Empowerment for Health, 2024)
Introduction: The global prevalence of knee osteoarthritis in older adults is expected to continue to increase until 2050. This increase was consistent with the prevalence rates in Malang. This progression is simultaneously controlled by Sustainable Development Goals. This service is a measure to support the government in the early detection of severity and education of knee osteoarthritis patients. Methods: The method was adopted through Community-Based Participatory Research at Puskesmas Pandanwangi, Malang. The respondents included 58 elderly people with symptoms of knee osteoarthritis. According to the Indonesian Rheumatology Association, the symptoms often experienced in Indonesia are pain, crepitus when moved, joint stiffness for more than 30 min, indications of enlargement of the knee area, tenderness of the bone edge, and no warmth in the synovium area. Results: The results of the average mapping show that respondents experienced knee osteoarthritis severity in the mild category or had a Laquesne index score of more than 1-4. Conclusion: The severity of osteoarthritis in Pandanwangi is influenced by age and body mass index. These respondents were educated on sitting up and down, stair step up, knee flexion, heel slide knee extension, and tight booster exercises to prevent severity at the next level. Exercise parameters were adjusted according to the respondent's condition for 8-12 weeks, 2-3 sessions per week.